ANALISIS TINGKAT KEPUASAN PELANGGAN TERHADAP KUALITAS LAYANAN PADA TOKO PRESPEKTIF ETIKA BISNIS ISLAM - Muhammad Alif Ramadhon (Irtifaq, 2023)
This study intends to analyze the level of customer satisfaction with service quality at Islamic Business Ethics Perspective Stores Jalan Irian Jaya 2-3 Cukir Jombang. The type of research used is qualitative research. The data used in this study were sourced from primary and secondary data. The data obtained were then analyzed using inductive and descriptive methods. Analysis of the data obtained from this study, the level of customer satisfaction with service quality at the Islamic Business Ethics Perspective Store, Jalan Irian Jaya 2-3 Cukir Jombang is in accordance with existing provisions and the overall transaction system is in accordance with the perspective of Islamic Business Ethics